Utilization of antenatal health care services and its impact on birth weight of newborn in rural area of Western Rajasthan, India - Uppadhaya, Sandeep Kumar; Agrawal, Neha; Bhansali, Suman; Garg, Kapil; Singh, Mahendra (International Journal Of Community Medicine And Public Health, 2017)
Background: Antenatal care is an important component of reproductive and child health but has not been utilized to the full extent in India. The study is aimed to assess the utilization of antenatal health care services by mothers and its impact on birth weight of their newborn. Methods: A community based cross sectional study was conducted in a rural area of Jodhpur, Rajasthan. A total of 198 women of study area who have delivered between 1st July 2013 to 30thJune 2014 (12 months period) were interviewed by pre-designed and semi-structured questionnaire by door to door approach. Results: Present study showed that 100% of mothers registered their pregnancy in any health facility and 56.6% were registered in 2nd trimester. Only 32.8% mothers had received four or more antenatal visits. Only 26.26% mothers had utilized full antenatal care (minimum four antenatal visits, minimum one TT and minimum 100 IFA tablet taken) during pregnancy. The prevalence of low birth weight was 12.6%. Proportion of LBW babies was more (15.9%) in mothers who had not availed of full antenatal care. This difference was statistically significantly (P<0.05). Conclusions: The important factors related to low utilization of Antenatal services were lower socioeconomic status, lower literacy of mothers, working mothers, parity and nuclear family. The findings of this study may be utilized by the health managers and health care providers to address the problem of low ANC coverage.